Principal Leadership in Improving Teacher Performance at Al-Misbah Senior High School Banda Aceh - Muklis; Badruzzaman; Kartika, Cindy Aulia (Dinasti Publisher, 2023)
The principal is a leader who has great influence and can determine the progress or failure of the school he leads and has administrative skills, has a fixed stance, and has the right to carry out each of his duties. To become a good school leader, one must make efforts to improve teacher performance through several programs that can foster educators. Therefore, to lead a school, the principal is required to have a good personality or character and have the ability to lead an educational institution. The formulation of the problem of this research is First, How is the responsibility of the principal at Al-Misbah High School in Banda Aceh. Second, What are the obstacles to teacher performance at Al-Misbah High School in Banda Aceh. The method used in this study is a qualitative approach. The informants in the study were the Vice Principal, School Committee, School Teachers, Parents. Data collection techniques, observation, research, and documentation. Websites that can be accessed via the internet, books and other written journals. The results of the research that has been conducted indicate that the personality of the principal in carrying out his function must have ethics in developing and advancing the school through teachers, knowledge but it needs to be emphasized, it does not mean that someone with low education is absolutely low in knowledge, the principal must work harder to be able to build the intelligence and skills of teachers to be able to produce educators, and motivation for teachers so that their performance can be improved and accounted for so that it becomes quality and students can improve their learning achievements. The conclusion from the results of the research above is that the leadership of the principal in improving teacher performance in order to be able to improve the qualities of teacher performance and knowledge, personality, and skills of teachers to be able to produce intelligent students.